Językowe formy budowania równowagi w relacjach międzynarodowych. Lingwistyczna analiza listu biskupów polskich do biskupów niemieckich z 1965 roku - Czachur, Waldemar (Forum Lingwistyczne, 2016)
Linguistic Forms of Balance Building in International Relations. A Linguistic Analysis of the Reconciliation Letter of the Polish Bishops to Their German Brothers of 1965 In his article, Waldemar Czachur makes an attempt of analysing the Reconciliation Letter of the Polish Bishops to their German Brothers of 1965 in terms of strategies aimed at building balance in international relations. The section which outlines the historical background of the letter and its political significance for Poland and the Polish-German relations is followed by linguistic analysis of subsequent parts of the letter to look at various balancing strategies between appreciating oneself and the recipient and protecting oneself and the recipient in the spirit of Goffman’s ritual equilibrium. Key words: 1965 Reconciliation Letter of the Polish bishops to German bishops, linguistic politeness, relationship building strategies, letter